Business Process Management 1: Introduction, Methods, and Information Systems (Second Edition) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2018)
The affiliation(s) and address(es) of the author(s): Dr. Archana Krishnan is presently Assistant Professor, Institute for Innovation in Technology and Management( Affiliated to Guru Gobind Singh Indraprastha University), D-29, Institutional Area, Janakpuri, New Delhi-110058. Dr. Archana Krishnan is a doctorate from Faculty of Management Studies (FMS), University of Delhi, New Delhi, India. The author has a B.E in Computer Science Engineering (2006, Anna University, Chennai, India) and an MBA in Human Resource and Systems (2008, Anna University, Chennai, India). Author’s interests include Total Quality Management, Organisational Behaviour, Human Resource Management.
Keywords: Information Technology; utilisation